Analisis Yuridis terhadap Pelanggaran Hak Cipta melalui Praktik Reupload Konten Tanpa Izin di Media Sosial di Indonesia - Raga Bahira Albantani; Teguh Abdurrohman Shodiq; Ikhwan Aulia Fatahillah (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study aims to conduct a legal analysis of the practice of unauthorized content reuploading as a form of copyright infringement on social media in Indonesia, as well as to evaluate the effectiveness of its enforcement in the digital context. The method used is normative legal research employing a legislative, conceptual, and comparative approach to international legal instruments. The results of the study indicate that the practice of reuploading constitutes a copyright infringement because it involves acts of reproduction, distribution, and public communication without the creator’s consent, thereby directly violating the economic rights and moral rights guaranteed under Law No. 28 of 2014 on Copyright. Furthermore, the open, fast, and cross-border nature of digital media amplifies the intensity and impact of such infringements compared to conventional forms. Law enforcement against this practice still faces significant challenges, including low public legal awareness, limited capacity of law enforcement agencies, and the suboptimal role of digital platforms in prevention. This study underscores the importance of strengthening adaptive regulations, enhancing the effectiveness of law enforcement, and integrating the role of digital platforms to create a copyright protection system that is more responsive to technological developments.